Implementing Technology Leadership Competency Standards for School Leaders: Enhancing Educational Quality in the Digital Age - Noormawati Kamaruddin,; Lutfiah Natrah Abbas@Ahmad, (Online Journal for TVET Practitioners, 2024)
Technological advancements are profoundly impacting various aspects of life, including education. This study investigates the necessity of Technology Leadership Competency Standards for school leaders to facilitate technology integration in schools. Employing a qualitative approach with basic interpretive methods, the study gathered insights through expert interviews. The findings reveal that clear guidelines, teacher collaboration, and adequate time for digitalization are essential for effective technology use in schools. Standards like the TPACK framework offer valuable guidance for school leaders. Uniform technology use across schools enhances teaching and learning outcomes. Implementing these standards ensures schools are prepared for future technological challenges and fosters ongoing growth and innovation in education